A lembrança como linguagem: intercruzando sonhos, memórias e histórias na narrativa dos velhos - Silva, Maria Madalena Martins da (2017)
The municipality of Sombrio in the extreme south of Santa Catarina state, left in its coastal landscape, an important cultural legacy built since pre-colonial times until the colonial period, with the arrival of the first european immigrants. Part of this patrimony is represented in the buildings and mosaics on the boardwalk of the municipality. It is also present in the memory of the old, whose narrative obtained through the methodology of Oral History, brought to the fore elements mnemonics individual and collective, that border and build a local history. The interlocking of dreams, stories and narratives of the old with the Material and Immaterial Patrimony established by the public power of Sombrio, made it possible to give visibility to a hybrid culture, dynamic and at the same time liquid and permanent, according to the paradigms of postmodernity. To understand how was this culture, the research guided in the investigation, through the methodology of oral history, about the heritage represented in the monuments exhibited in the promenade of the Sombrio, from the tiles up to the monuments built, in order to understand if these manifestations were a part of the universe mnemonic of the old. We start from the premise that the elements of the cultural heritage highlighted by the public power, have their root in a past consolidated by the memory of the oldest. For this, it conducted a field survey and documentary, where he sought to understand in depth, what were these elements. The interviews enabled a vision is differentiated and individualized from the heritage place, without, however, losing the notion of collectivity, that was behind each narrative presented, which portrayed a time in the past, bathed in this. As a result be found that the material and immaterial heritage established by the public power of Sombrio, integrates the memory of old people of that locality. The search qualified and expanded on the importance of memory and identity, which are highlighted through the language and culture of a society, in the construction, re-signification and valorization of the cultural heritage site.